PLANNING FOR THE C.P.A. EXAMINATION IN THE UNITED STATES. - Allyn, Robert G. (The Accounting Review, 1964)
Abstract As in any examination, the wrong attitude toward the Certified Public Accountants (CPA) examination often hampers the job of taking it and may actually affect the results. One result that an examining board does not want is 100 per cent penny accuracy. A Board of Examiners, as representatives of the profession, wants men who can think and make sound, effective judgments, though the final judgment or solution may not be 100 per cent accurate in terms of the arithmetic. A narrow, petty attention and an almost subservient consideration to details, is not the hallmark of a professional accountant. The examiner wants to know what the candidate knows about the principles of accounting and their applicability to the variety of situations to which he is being exposed in the CPA questions and problems. As the uniform CPA examination is geared to abilities of an average senior accountant, it is reasonable to conclude that most candidates who earn a baccalaureate degree in most colleges today will have the mental ability to pass the examination conducted by the American Institute of Certified Public Accountants.